Thermally Affected Zone (TAZ) Assessment in Open-Loop Low-Enthalpy Groundwater Heat Pump Systems (GWHPs): Potential of Analytical Solutions. (27th April 2020) - Gizzi, Martina; Taddia, Glenda; Abdin, Elena Cerino; Russo, Stefano Lo
Abstract : Thermal perturbation produced in the subsurface by open-loop groundwater heat pump systems (GWHPs) must be predicted and constantly controlled, especially in the shallow aquifers of more densely urbanized areas, in order to guarantee plants' long-term sustainable use and to avoid adverse effects on adjacent geothermal systems. Transient conditions in the flow dynamic can be successfully modelled by means of numerical modelling tools. However, for small plants in suitable hydrogeological systems, an alternative tool for predicting the thermally affected zone (TAZ) around the injection well can be found in analytical solutions for steady advective transport in a shallow aquifer. The validity of using steady analytical solutions to predict the TAZ development at the end of two different cooling seasons (2010 and 2016) was tested in the Politecnico di Torino GWHP system (NW Italy). When fixing the constant thermal difference (Δ T ) between the injection and abstraction wells at 5°C, results revealed that a rather reliable assessment of the TAZ of Politecnico di Torino GWHPs, in Turin shallow aquifer, can be performed by plotting the cumulative distribution function of the injected discharge rate (Q ) and setting 63% as a steady value.